Razlogi za neuporabo storitev splošnih knjižnic - Švab, Katarina (Knjižnica, 2020)
Purpose: Librarians have always been faced with the question of how to get non-users into the library. This question remains relevant also today. The aim of this article is to present opinions and reasons of parents of preschool children for not visiting the libraries, their perception of the library and expectations from the library in order to encourage them to visit the library with their preschool children.Methodology/approach: To obtain more in-depth reasons and data, we conducted a pilot study as a semi-structured personal interview. In February 2020, we interviewed twenty parents of preschool children in various parts of Slovenia who do not attend the library with their children.Results: Although the interviewed group of parents does not visit the library, they have a good opinion of the library, its services and librarians. As their main reason for not using the library services they highlighted the lack of time, problems with accessibil-ity or parking and that their children are still too young to visit the library. Suggested improvements were focused on the events (workshops, social events) that could be at-tended together with the children and not to the library collection. Parents expressed that instead of adaptations in the equipment, they would prefer to have a place in a library (a corner) where they would feel comfortable and not disturbing for others with the sounds and noise their children are causing.Research limitations: The data from the pilot study cannot be generalized, even if the interviews were conducted in different parts of Slovenia. Comments and opinions from non-users are an opportunity to reflect on existing and possible new library services and planned promotion.Originality/practical implications: There are not many qualitative researches with non-library users in Slovenia. Results of this pilot study can be a starting point for further researches in the local communities and for planning new library services, for potential users to respond to their expectations and needs.
Keywords: knjižnične storitve; library services; neuporabniki; non-users; parents; predšolski otroci; preschool children; public libraries; splošne knjižnice; starši